2024
DOI: 10.3389/fimmu.2024.1326354
|View full text |Cite
|
Sign up to set email alerts
|

Regulation mechanisms of disulfidptosis-related genes in ankylosing spondylitis and inflammatory bowel disease

Lin Li,
Haixin Fang,
Fuzhen Li
et al.

Abstract: IntroductionDisulfidptosis is a recently identified form of cell death that contributes to maintaining the internal environment balance of an organism. However, the molecular basis of disulfidptosis in ulcerative colitis (UC), ankylosing spondylitis (AS), and Crohn’s disease (CD) has not been thoroughly explored.MethodsFirstly, the differentially expressed genes (DEGs) and disulfidptosis-associated genes (DAGs) were obtained through differential analysis between diseases (AS, CD, and UC) and control groups. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
0
0
Order By: Relevance
“…Another study also confirmed that thiols with reducing properties were significantly reduced in gingival tissues of periodontitis patients ( Cerkezi et al, 2024 ), and that this reducing compound plays a crucial role in resistance to oxidative stress. Furthermore, disulfidptosis has been progressively studied in inflammatory diseases such as obligatory myelitis and ulcerative colitis ( Li et al, 2024 ; Xiong et al, 2024 ). Thus, the state of oxidative stress in periodontitis and the changes in disulfide levels allow us to reasonably hypothesize that the development of periodontitis may be associated with disulfidptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also confirmed that thiols with reducing properties were significantly reduced in gingival tissues of periodontitis patients ( Cerkezi et al, 2024 ), and that this reducing compound plays a crucial role in resistance to oxidative stress. Furthermore, disulfidptosis has been progressively studied in inflammatory diseases such as obligatory myelitis and ulcerative colitis ( Li et al, 2024 ; Xiong et al, 2024 ). Thus, the state of oxidative stress in periodontitis and the changes in disulfide levels allow us to reasonably hypothesize that the development of periodontitis may be associated with disulfidptosis.…”
Section: Introductionmentioning
confidence: 99%